Phase coexistence induced strong piezoelectricity in K0.5Na0.5NbO3-based lead-free ceramics. Issue 28 (26th June 2019) - Yang, Yang; Wang, Hua; Li, Yao; Zheng, Qiaoji; Liao, Jie; Jie, Wenjing; Lin, Dunmin
Abstract : For perovskite ceramics, the ferroelectric phase boundary plays an important role in improving the piezoelectricity of the materials. Abstract : For perovskite ceramics, the ferroelectric phase boundary plays an important role in improving the piezoelectricity of the materials. In this work, (1 − x )(K0.5 Na0.5 )NbO3 − x [NaSbO3 + Bi0.5 (Na0.8 K0.2 )0.5 (Zr0.5 Hf0.5 )O3 ] lead-free ceramics with R-O-T ferroelectric phase coexistence were developed and the relationship between the phase structure and piezoelectricity was investigated in detail. As x increases, the transition temperature of the rhombohedral and orthorhombic phases (TR-O ) increases, while the orthorhombic–tetragonal phase transition temperature (TO-T ) decreases. When 0.04 ≤ x ≤ 0.05, three ferroelectric phases (R-O-T) coexist near room temperature in the ceramics. Due to the highly consistent orientation of the ferroelectric dipole and the free energy flattening and a low energy barrier induced by the coexistence of three ferroelectric phases (R-O-T), excellent piezoelectric performances of d 33 = 452 pC N −1, k p = 63% and ε r = 4414 are achieved at x = 0.04. Our study suggests that compared with two ferroelectric phase boundaries (R-O and O-T), the coexistence of the three ferroelectric phases (R-O-T) can effectively enhance the piezoelectric properties of (K0.5 Na0.5 )NbO3 -based ceramics.